2019
DOI: 10.1136/bmjopen-2018-023995
|View full text |Cite
|
Sign up to set email alerts
|

Association of lifestyle modification and pharmacological adherence on blood pressure control among patients with hypertension at Kenyatta National Hospital, Kenya: a cross-sectional study

Abstract: ObjectiveAssociation of lifestyle modification and pharmacological adherence among patients with hypertension attending a national referral hospital in Kenya.DesignDescriptive, cross-sectional.SettingMedical wards and outpatient clinic of a national referral hospital.ParticipantsPatients (n=229) diagnosed with primary hypertension for at least 6 months.Primary outcomesClinical makers, cholesterol levels, anthropometrics, lifestyle/dietary habits adjusted for age, gender and education; antihypertensive adherenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
4
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 82 publications
4
47
4
3
Order By: Relevance
“…However, the result of this study was lower than a study conducted at Mizan Tepi hospital which was 66.7% (25), Durame hospital which was 72.7% (16), and Addis Ababa which was 77% (10). In contrast, the nding of this study was higher than a study conducted at Hiwot Fana and Jugola hospital which was 37.9% (26), Nekemite hospital (27) which was 31.1%, Saudi which was 25.6% (33), Ghana which was 28% (35) and Iran which was 27% (28). This discrepancy might be due to differences in life style, culture, economic status, access to health care facilities and level of education of the general public.…”
Section: Discussioncontrasting
confidence: 70%
“…However, the result of this study was lower than a study conducted at Mizan Tepi hospital which was 66.7% (25), Durame hospital which was 72.7% (16), and Addis Ababa which was 77% (10). In contrast, the nding of this study was higher than a study conducted at Hiwot Fana and Jugola hospital which was 37.9% (26), Nekemite hospital (27) which was 31.1%, Saudi which was 25.6% (33), Ghana which was 28% (35) and Iran which was 27% (28). This discrepancy might be due to differences in life style, culture, economic status, access to health care facilities and level of education of the general public.…”
Section: Discussioncontrasting
confidence: 70%
“…A study from Uganda showed that awareness about hypertension was 28.2%, and only 9.4% of participants had controlled their BP [ 35 ]. A study conducted in Kenya showed that about 53.6% of patients believed they should stop taking antihypertensive medication once hypertension is controlled [ 85 ]. A study from Malawi showed that 62% of the hypertensive patients were aware of their blood pressure [ 86 ].…”
Section: Resultsmentioning
confidence: 99%
“…This was consistent with reports from other studies which noted BP control rates of between 34 and 49%. 20 , 50 , 51 Elevated BP is the number one risk factor for cardiovascular diseases and the control and treatment of hypertension can result in a reduced incidence of complications. 52 Health workers at Mutare Provincial Hospital OPD must devise strategies to promote the control of hypertension among patients.…”
Section: Discussionmentioning
confidence: 99%